Computationally Driven Discovery of a Family of Layered LiNiB Polymorphs. Issue 44 (26th September 2019) - Gvozdetskyi, Volodymyr; Bhaskar, Gourab; Batuk, Maria; Zhao, Xin; Wang, Renhai; Carnahan, Scott L.; Hanrahan, Michael P.; Ribeiro, Raquel A.; Canfield, Paul C.; Rossini, Aaron J.; Wang, Cai‐Zhuang; Ho, Kai‐Ming; et al.
Abstract: Two novel lithium nickel boride polymorphs, RT ‐LiNiB and HT ‐LiNiB, with layered crystal structures are reported. This family of compounds was theoretically predicted by using the adaptive genetic algorithm (AGA) and subsequently synthesized by a hydride route with LiH as the lithium source. Unique among the known ternary transition‐metal borides, the LiNiB structures feature Li layers alternating with nearly planar [NiB] layers composed of Ni hexagonal rings with a B–B pair at the center. A comprehensive study using a combination of single crystal/synchrotron powder X‐ray diffraction, solid‐state 7 Li and 11 B NMR spectroscopy, scanning transmission electron microscopy, quantum‐chemical calculations, and magnetism has shed light on the intrinsic features of these polymorphic compounds. The unique layered structures of LiNiB compounds make them ultimate precursors for exfoliation studies, thus paving a way toward two‐dimensional transition‐metal borides, MBenes. Abstract : By design : Novel lithium nickel borides with unique layered structures were theoretically predicted and synthesized. Their structures are composed of [NiB] layers with different topologies alternating with layers of Li cations (see picture). These compounds are ultimate precursors for further exfoliation to generate 2D transition‐metal borides, known as MBenes.